The long reach of English law: a case of incidental transplantation of the English law concept of vicarious liability into Thailand's Civil and Commercial Code. Issue 2 (3rd July 2018) - Reekie, Adam; Reekie, Surutchada
Abstract : Thailand's Civil and Commercial Code, introduced in 1925, represents a voluntary major legal transplantation by which Thailand adopted a complete new code based on foreign models. This article traces the development of Section 425, which confers liability on employers vicariously for the wrongful acts of their employees, and reveals that the concepts present in the stated sources of the provision do not match those represented by the section in its final form. Rather, the concepts hint at another source, unstated and hitherto uncredited as a source of this part of the Code, the English law doctrine of vicarious liability. This conclusion sheds new light on the complex process of legal transplantation and legal reform in Thailand during the early twentieth century, challenging the orthodox view, and has wider implications for those considering the societal factors which guide and shape legal reform.